The transversal systems and their impact on the efficiency and effectiveness of the Judicial Power - Montoya Muñoz, Juan Carlos (2012)
Transversal systems are master lines that report the routine activities of a public or private organization. This article addresses the form and manner in which the transversal systems, such as financial management, public planning, citizen participation, supervision and monitoring and State reform provide insight on the performance of the Judiciary and on their impact in said State branch. The strengthening of the transversal systems and their practical application in the Judiciary can endow it with efficiency (the capacity to achieve a goal making use of the best possible means) and efficacy (the capacity to achieve the desired or expected effect regardless of the resources or means used) as long as they are articulated with its vision, mission, strategic plan, working environment and its cohesive relationship with the remaining organizations of the justice system